Experimental and quantum chemical studies of anionic analogues of N-heterocyclic carbenes. Issue 22 (21st May 2018) - Niu, Haoyu; Mangan, Robert J.; Protchenko, Andrey V.; Phillips, Nicholas; Unkrig, Wiebke; Friedmann, Christian; Kolychev, Eugene L.; Tirfoin, Rémi; Hicks, Jamie; Aldridge, Simon
Abstract : A combination of quantum chemical and synthetic/crystallographic methods have been employed to probe electronic structure in two series of anionic ligands related to the well-known NHC donor class. Abstract : A combination of quantum chemical and synthetic/crystallographic methods have been employed to probe electronic structure in two series of anionic ligands related to the well known N-heterocyclic carbene (NHC) class of donor. Analyses of (i) the respective frontier orbital energies/compositions for the 'free' ligands and the results of ETS-NOCV studies of the bonding in model group 11 complexes; and (ii) the structural metrics for (new) linear gold(i ) compounds, have been used to probe the bonding in complexes of NHC ligands which incorporate a backbone-appended weakly-coordinating anion component (WCA-NHCs) and in systems featuring the isoelectronic (formally anionic) diazaborolyl ligand family. Key findings are that WCA-NHC ligands – in which the anionic component is attached to the ligand heterocycle via a methylene (CH2 ) spacer – offer electronic (and steric) properties which are largely unperturbed from their 'simple' NHC counterparts, while diazaborolyl donors (in which the negative charge is formally located at the boron donor atom) offer significantly stronger σ-donation and a very high trans influence.